Direct Observation of Sulfur Radicals as Reaction Media in Lithium Sulfur Batteries. Issue 3 (9th January 2015) - Wang, Qiang; Zheng, Jianming; Walter, Eric; Pan, Huilin; Lv, Dongping; Zuo, Pengjian; Chen, Honghao; Deng, Z. Daniel; Liaw, Bor Yann; Yu, Xiqian; Yang, Xiaoqing; Zhang, Ji-Guang; et al.
Abstract : Lithium sulfur (Li-S) battery has been regaining tremendous interest in recent years because of its attractive attributes such as high gravimetric energy, low cost and environmental benignity. However, it is still not conclusively known how polysulfide ring/chain participates in the whole cycling and whether the discharge and charge processes follow the same pathway. Herein, we demonstrate the direct observation of sulfur radicals by using in situ electron paramagnetic resonance (EPR) technique. Based on the concentration changes of sulfur radicals at different potentials and the electrochemical characteristics of the cell, it is revealed that the chemical and electrochemical reactions in Li-S cell are driving each other to proceed through sulfur radicals, leading to two completely different reaction pathways during discharge and charge. The proposed radical mechanism may provide new perspectives to investigate the interactions between sulfur species and the electrolyte, inspiring novel strategies to develop Li-S battery technology.